Relationship Between Personal Hygiene and the Incidence of Diarrhea in Children - Komariah, Komariah; Aziza, Nurul; Putri, Dian Utama Pratiwi; Budiati, Endang (Global Health Science Group, 2025)
Diarrhea is increasing frequency of defecate as much as 3 or more in 1 day and the consistency more liquid from normal humans. Diarrhea is usually a symptom of intestinal infection, which can be caused of some bacteria, virus, parasite. The infection are disperse through contaminated food and drink, or people to people as a effect of the poor hygiene. This research study is aimed to know the correlation of incidence of diarrhea with personal hygiene in children at regional Lemong public health center in 2023. Method used on this research is quantitative method with a cross sectional study approach. The sample is determined by probably sampling and sample obtained 55 respondents. The tools used to collect data in this research is questionnaire sheet then analyzed by Chi square statistical tests. The data is analyzed with statistic software. Statistical test results found a significant correlation or relationship between incindence of diarrhea and the behavior of washing hand with soup (ρ-value =0,001), significant correlation between the incidence of diarrhea with the behavior of maintaining hand and nail hygiene (ρ-value <0,002), significant correlation between the incidence of diarrhea with defecation behavior (ρ-value <0,048). It can be concluded that personal hygiene is related to the incidence of diarrhea in regional of Lemong public health center, west coast district in 2023. So it can be concluded that personal hygiene is related to the incidence of diarrhea in regional of the Lemong Public Health Center, Pesisir Barat District in 2023.